Resonator-free optical bistability based on epsilon-near-zero mode - Kim, Myunghwan; Kim, Sangin; Kim, Soeun (Scientific Reports, 2019)
A majority of existing research on optical bistability rely on resonant schemes using nonlinear materials, which inevitably require a trade-off between the switching intensity and response time. In this work, we propose a novel non-resonant scheme, which utilizes strong light enhancement of the epsilon-near-zero (ENZ) mode to realize optical bistability. We used graphene as a non-linear ENZ material and designed an integrated optical bistability device composed of a graphene-embedded Si waveguide, which supports an ENZ mode. The proposed scheme can overcome the trade-off necessary in resonance-based optical bistability, and the designed optical bistability device simultaneously allows for a short response time (~200 fs) and low switching intensity (~700 kW/cm 2 ).